DARK SOIL PITS AND GRAVES IN VOLCANIC CAVE C6.1, KRONG NO, DAK NONG PROVINCE: DOCUMENTATION AND DISCUSSION - Cao, Bao Lam (Trường Đại học Đà Lạt, 2024)
Dark soil pits and graves are critical documents discovered in volcanic cave C6.1. As a result of the investigation and excavation of cave C6.1 conducted in 2017, 2018, and 2019, we have discovered vestiges of nine dark soil pits and seven relatively intact graves, together with teeth and other human remains scattered in the cultural layer. This is an important source of information on the racial composition of the prehistoric inhabitants of the Central Highlands during the Neolithic period, as well as the paleoenvironment, environmental adaptations, and flora and fauna that prehistoric inhabitants exploited for their livelihoods. This article introduces documents and reconstructs the socioeconomic picture of the prehistoric inhabitants of cave C6.1. It also contributes scientific documents for the general conservation and promotion of heritage to develop sustainable cultural tourism in Dak Nong Province.